Perro peruano - Meza Manzano, Renzo Enrique (2024)
The project Perro peruano (Peruvian Dog) represents generic dogs as victims of obvious mistreatment and/or malnutrition. Despite the title, these dogs are not meant to look like the hairless dog, since we’re not focusing on the breed, but rather on the dogs belonging to Peru, using the term to refer to their nationality. The intention behind this idea is to connote the treatment that the dogs in our country receive from the people. It reflects the way in which we look at our animals, more specifically dogs, through looks of fear and sadness; their debilitating and dying bodies with tails behind their hind legs reflect an image of submission caused by mistreatment. To set up examples from Peru, they go through hunger, due to lack of food; illness, caused by overpopulation (also caused by irresponsible owners) and the way in which these are controlled by civilians, which is by beating them to death, poisoning them or using fire, even with some municipalities contributing to these measures. This is why we are positioning people as the main inflictors of this suffering and the reason why the eyes in the pieces tend to be looking straight ahead, it’s because they seek to look at the spectator as if they were the ones responsible for the pain, fear and suffering they convey. To support this we have resorted to the dramatism of achromatism in several of the pieces and, due to the prevalence of color, the traditional materials used to compose the sculptures (resin and plaster) are moved to the sidelines.